Analisis Yuridis Terhadap Perbuatan Notaris Yang Tidak Membacakan Akta (Studi Kasus Putusan Mpwn Sumatera Utara Nomor 7 /MPWN.Provinsi Sumatera Utara/X/2016) - Syamsi, Notarianul (Recital Review, 2022)
This is a descriptive research employed normative jurisdiction research type using primary and secondary data obtained from field research. The results of this research demonstrated that the impact of Notary who did not read out the deed created a gradated deed into Privately Made Deed and caused detriments to the parties. Notary had violated article 16. paragraph 1 letter MUUJN (Rules of Notary Profession). It was responsibility of a Notary that a non-read out deed causing compensation that can be requested by the appearer to the Notary in accordance with article 44. paragraph 5 UUJN (Rules of Notary Profession). Protection against violation of reading out this deed has been stated in the Decree of MPWN (Region Supervisory Council of Notary) North Sumatera Number 7 / MPWN Provinsi Sumatera Utara / X / 2016. The conclusion demonstrated that the Notary caused detriments to the appearers due to a non-read out deed to the appearers. What Notary did by not reading out deed violated the obligation. What the Notary did not do violated the article 16, paragraph 1 letter M. It was recommended that a Notary should be more thorough in carrying out the obligations and authorities given to them. Abstrak Hasil dari penelitian diperoleh bahwa dampak dari notaris tidak membacakan akta mengakibatkan akta terdegradasi menjadi akta dibawah tangan sehingga merugikan para pihak. Notaris telah melanggar pasal 16 ayat 1 huruf M UUJN yang merupakan tanggung jawab notaris terhadap akta yang tidak dibacakan menimbulkan suatu ganti kerugian yang dapat diminta oleh penghadap kepada notaris sesuai pasal 44 ayat 5 UUJN . Perlindungan terhadap pelanggaran pembacaan akta ini telah diberikan dalam Putusan MPWN Sumatera Utara Nomor 7/MPWN Provinsi Sumatera Utara/X/2016.Kesimpulan yang diperoleh notaris membuat kerugian kepada para penghadap karena tidak dibacakan kepada para penghadap. hal yang dilakukan notaris dengan tidak membacakan akta melanggar kewajiban yang tidak dilakukan oleh notaris yang melanggar pasal 16 ayat 1 huruf m.disarankan agar notaris lebih teliti dalam melakukan kewajiban dan kewenangan yang diberikan kepadanya.